The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1051/0004-6361/201220902
|View full text |Cite
|
Sign up to set email alerts
|

High angular resolution imaging and infrared spectroscopy of CoRoT candidates

Abstract: Context. Studies of transiting extrasolar planets are of key importance for understanding the nature of planets outside our solar system because their masses, diameters, and bulk densities can be measured. An important part of transit-search programmes is the removal of false-positives. In the case of the CoRoT space mission, the majority of the false-positives are removed by a detailed analysis of the light curves and by seeing-limited imaging in-and out-of-transit. However, the critical question is how many … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 26 publications
(33 reference statements)
0
23
0
Order By: Relevance
“…The aim of these observations was to find out whether there are any stars within a few arcsec from the target that are bright enought to be FPs (see Guenther et al 2013 for details on this method). We detected two previously unknown stars.…”
Section: 3)mentioning
confidence: 99%
“…The aim of these observations was to find out whether there are any stars within a few arcsec from the target that are bright enought to be FPs (see Guenther et al 2013 for details on this method). We detected two previously unknown stars.…”
Section: 3)mentioning
confidence: 99%
“…Bardalez Gagliuffi et al (2014) analyzed a sample of 815 M and L dwarf spectra taken with IRTF SpeX in order to locate blended stellar companions with relatively low effective temperatures (also see Burgasser et al 2010). Guenther et al (2013) used CRIRES on the Very Large Telescope to identify approximately twenty planet-hosting stars in the CoRoT sample with blended spectra from close stellar companions. Kolbl et al (2015) observed planet-hosting stars from the Kepler survey with optical Keck HIRES spectroscopy in order to search for binary companions with relative radial velocities greater than 10 km s −1 such that the secondary absorption lines are Doppler shifted.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been argued that the exclusion of FPs at distances larger than 1-2 arcsec is sufficient to show that the star is the transiting object, detailed studies show that AO-imaging is essential for confirming transiting planets, otherwise the probability for FPs is unacceptably high (Guenther et al 2013 [13]). We thus obtained images with PISCES, the adaptive optics imager of the Large Binocular Telescope (LBT).…”
Section: Ground-based Observationsmentioning
confidence: 99%